Isolation of natural radiation to indoor applications with wood-based products: a case study of the central region of Portugal. (August 2015) - Nunes, J.; Silva, J.; Freitas, H.; Neves, L.; Pereira, A.
Abstract : Radon is a radioactive gas that occurs naturally, causing severe consequences to human health. In fact, some studies have shown that high indoor radon values can have an impact on the development of cancer. The gas can enter the inside of buildings though cracks. In the construction industry, wood-based products are used frequently because of the fact that they are made from natural resources and have various functions in a building context. The present study led to the development of an optimised wood-based product with a new function, allowing a real radon resistance ability of over 95%. This product was developed for application on buildings' floors and is intended to prevent the penetration of radon gas inside the buildings. The solution demonstrated higher efficiency than current commercially available products, revealing itself to be an excellent and competitive alternative to already existing active and passive mitigation methods in the market.